Rights, regulation and redistribution: The global politics of investment protection. (April 2019) - Koivusalo, Meri
The analysis of the implications of trade and investment agreements usually follows either economic policy modelling or the analysis of specific arbitration cases. These two approaches are often less helpful from the perspective of more systemic impacts or other policy aims as the potential concerns tend to be accounted for on the basis of a single issue (e.g. tobacco) or case or are carved out from particular agreements. The 3R framework on rights, regulation and redistribution provides a broader framework to analyse trade and investment agreements in relation to other policy aims, such as health or social policies and protection. I apply here the 3R framework to examine how and on what basis investment liberalisation and protection, as negotiated by the European Union, could affect both global and national policy space for health and social policies.